2005
DOI: 10.1007/s10577-005-1005-6
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion proteins are present in centromere protein bodies associated with avian lampbrush chromosomes

Abstract: Proteins of sister chromatid cohesion are important for maintenance of meiotic chromosome structure and retention of homologous chromosomes in bivalents during diplotene. Localization of the cohesion proteins within nuclei of growing oocytes merits special attention, particularly in avian oocytes, in which diplotene chromosomes assume the form of lampbrush chromosomes (LBCs). We performed indirect immunostaining using antibodies against cohesins SMC1!, SMC1", SMC3, Rad21, and the SA/STAG family on chaffinch, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…To detect centromere positions on chicken and quail LBCs, preparations were stained with rabbit polyclonal antibodies K828 or K854 against STAG2 and Rad21 cohesin subunits, correspondingly, as previously described (Krasikova et al 2005). After image acquisition, slides were washed in 4× SSC, 0.1 % Tween 20 at 42°C, dehydrated in 96 % ethanol, air-dried, and then used for FISH.…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
“…To detect centromere positions on chicken and quail LBCs, preparations were stained with rabbit polyclonal antibodies K828 or K854 against STAG2 and Rad21 cohesin subunits, correspondingly, as previously described (Krasikova et al 2005). After image acquisition, slides were washed in 4× SSC, 0.1 % Tween 20 at 42°C, dehydrated in 96 % ethanol, air-dried, and then used for FISH.…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
“…Centromere protein bodies of chicken, quail and turkey lampbrush chromosomes are very small (approximately 1 μm in diameter) and look like centromere granules of amphibian lampbrush chromosomes (Krasikova et al 2006Macgregor 2012). A centromere protein body can be identified by marker components such as subunits of cohesin complex and component of synaptonemal lateral element SYCP3 (Krasikova et al 2005). However, the accurate location and specific functions of centromere protein bodies in a centromere region of avian lampbrush chromosomes are still puzzling Krasikova and Gaginskaia 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(4) Finally, in birds, cohesion proteins aggregate into protein bodies that assemble adjacent to centromeres (Krasikova et al, 2005). These protein bodies vary in size among and within bird species (Krasikova et al, 2006) and it has been suggested that they may interfere with spindle attachment to the centromere (Rutkowska and Badyaev, 2008).…”
Section: Introductionmentioning
confidence: 99%